1995
DOI: 10.1038/376058a0
|View full text |Cite
|
Sign up to set email alerts
|

Mesoderm induction in Xenopus caused by activation of MAP kinase

Abstract: Mesoderm induction is a critical early step in vertebrate development, involving changes in gene expression and morphogenesis. In Xenopus, normal mesoderm formation depends on signalling through the fibroblast growth factor (FGF) tyrosine kinase receptor. One important signalling pathway from receptor tyrosine kinases involves p21ras (ref. 5). Ras associates with the serine kinase c-Raf-1 in a GTP-dependent manner, and this complex phosphorylates and activates MAPK/ERK kinase (MEK), a protein kinase with dual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
142
0
1

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(150 citation statements)
references
References 32 publications
7
142
0
1
Order By: Relevance
“…Concomitant decrease of Akt/PKB and PLCg-1 activation in the mutant connects FGF signaling and epithelial di erentiation with the PI 3-kinase pathway. Comparing Akt/PKB and PLCg-1 activation with the activation of MAPK/Erk, the major signal transduction pathway of FGF signaling during gastrulation (Northrop et al, 1995;Umbhauer et al, 1995), suggested that the PI 3-kinase pathway may have a special role in the early epithelial di erentiation of the embryoid body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitant decrease of Akt/PKB and PLCg-1 activation in the mutant connects FGF signaling and epithelial di erentiation with the PI 3-kinase pathway. Comparing Akt/PKB and PLCg-1 activation with the activation of MAPK/Erk, the major signal transduction pathway of FGF signaling during gastrulation (Northrop et al, 1995;Umbhauer et al, 1995), suggested that the PI 3-kinase pathway may have a special role in the early epithelial di erentiation of the embryoid body.…”
Section: Discussionmentioning
confidence: 99%
“…A leading role is attributed to the MAPK/ERK pathway, in insect (Gabay et al, 1997) and vertebrate development (Northrop et al, 1995;Umbhauer et al, 1995). Another signaling pathway, that leads through phosphatidyl-inositol 3-kinase (PI 3-kinase) and Akt/PKB, is also induced by the same receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Blocking the function of Ras, Raf, MEK and ERK inhibits mesoderm formation. Overexpression of the constitutively activated forms of these signaling components induces the expression of mesodermal markers in an animal cap assay (Whitman & Melton 1992;MacNicol et al 1993;LaBonne & Whitman 1994;Gotoh et al 1995;LaBonne et al 1995;Umbhauer et al 1995). A recent study has suggested that the spatial pattern of ERK activation closely resembles the expression of FGF (Christen & Slack 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have shown that mesoderm induction by FGF in Xenopus embryogenesis requires activation of the MAPK pathway (Gotoh et al, 1995b;LaBonne et al, 1995;Umbhauer et al, 1995). We considered two explanations for our ®nding that only DN Grb2 mutants could inhibit Erk1 activation in 293 cells (data not shown), while NckKSH2 as well as the DN Grb2 mutants could inhibit the induction of a mesodermspeci®c gene in Xenopus animal caps (Figure 1b).…”
Section: E Ect Of Dn Adapters On Erk1 Induction By Efgf In 293 Cells mentioning
confidence: 84%
“…Microinjection of RNA encoding dominantnegative mutants of Ras or Raf, or encoding a MAPKspeci®c phosphatase, into Xenopus embryos has also implicated Ras, Raf and MAPK in mesoderm induction by FGF (Gotoh et al, 1995b;LaBonne et al, 1995;MacNicol et al, 1993;Umbhauer et al, 1995;Whitman and Melton, 1992). Although a peptide fragment of the chicken bFGFR was shown to bind to the SH2 domain of Grb2 with moderate a nity (Ward et al, 1996), intact FGFRs do not bind directly to SH2/SH3 adapter proteins.…”
Section: Introductionmentioning
confidence: 99%